2020
DOI: 10.1038/s41598-020-75416-8
|View full text |Cite|
|
Sign up to set email alerts
|

Microvascular impairment as a biomarker of diabetic retinopathy progression in the long-term follow up in type 1 diabetes

Abstract: This study aimed to explore differences in vascular and structural parameters using optical coherence tomography angiography in patients with type 1 diabetes (DM1) with mild signs of diabetic retinopathy (DR) over a two-year follow-up period. Parafoveal vessel density (PVD) and foveal avascular zone (FAZ) area were analyzed. The thickness of three predefined retinal slabs was measured, including the inner limiting membrane (ILM)–inner plexiform layer (IPL), IPL–inner nuclear layer (INL), and the IPL–outer nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
0
10
2
Order By: Relevance
“…In addition, the area of the foveal avascular zone (FAZ) showed no significant changes over time in both groups. As already reported, the impairment of DCP represents a biomarker for both early diagnosis and risk of progression in DR [ 124 ].…”
Section: Clinical Datamentioning
confidence: 83%
“…In addition, the area of the foveal avascular zone (FAZ) showed no significant changes over time in both groups. As already reported, the impairment of DCP represents a biomarker for both early diagnosis and risk of progression in DR [ 124 ].…”
Section: Clinical Datamentioning
confidence: 83%
“…Compared with 40 eyes of age-matched healthy subjects, the study group showed a significant reduction in the SCP, DCP, and RPC VD. OCTA depicted a more significant impairment of the DCP than the SCP in COVID-19 patients compared to controls, as also occurs in diabetic retinopathy [ 45 ] and other systemic vasculopathy. The authors hypothesise that COVID-19-related thrombotic microangiopathy could cause vascular perfusion damage to the SCP and RPC, resulting in restriction in axoplasmic flow and subsequent retinal structural loss.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies analyzing microvascular parameters of the SCP, ICP and DCP in patients with diabetic retinopathy found a significant reduction in vessel density across all three distinct capillary plexuses 30 , with the degree of vessel density reduction corresponding to the severity of diabetic retinopathy and associated vision loss 30 36 . Recently, the important role of ICP has been distinctly demonstrated with significantly decreased ICP vessel density, perfusion, and blood flow in patients with worsening DR 9 , 31 , 37 .…”
Section: Discussionmentioning
confidence: 99%